HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN KESIAPAN MENGHADAPI MENARCHE PADA SISWI KELAS VII DI SMP 1 PLAYEN GUNUNGKIDUL - Ayu, Suci Musvita; Djannah, Sitti Nur; Wardani, Yuniar (Universitas Ahmad Dahlan, 2010)
Background: Adolescent is a periode where many physical changes and environmentaldemainds occurings. For a girl, the most visible changes is the beginning of menarche or firstmenstruation. Because menarche is definitely happened to every girl. Its necessary for a girl tohave many sources of social support to help her reduce anxiety during her menarche periodeand decrease her readiness on that situasion. The goal is to find of relationship between socialsupport and readiness on menarche at VII grade of SMP 1 Playen Gunungkidul.Method: This was an analytical observation research using cross sectional approach. Theresearch subjects were 26 students of VII grade of SMP 1 Playen, 12-13 years old and havingmenarche. Sampel were taken using accidental sampling techniques, data analysis used ChiSquare.Result : There was relationship between social support and readiness on menarche withcorrelation coefficient was 0,599 and significance/Asymp. Sig was 0,006 which compared by a=0,05 so P value < 0,05. from 26 subjects, 65,4 persen had sufficient social support level and 73persen subjects had sufficient level of readiness on menarche.Conclusion : There was relationship between social support and readiness on menarche at VIIgrade of SMP 1 Playen Gunungkidul Yogyakarta andd readiness on menarche. 65,4 persen hadsufficient social support level and 73 persen subjects had sufficient level of readiness onmenarche.Key Word: Social Support, Readiness On Menarche, Student